COMPARATIVE HPLC-MS ANALYSIS OF PHENOLICS FROM ACHILLEA DISTANS AND ACHILLEA MILLEFOLIUM AND THEIR BIOACTIVITY - BENEDEC, Daniela; POPICA, Iulia-Elena; ONIGA, Ilioara Elena; HANGANU, Daniela; DUMA, Mihaela; SILAGHI-DUMITRESCU, Radu; BISCHIN, Cristina; VLASE, Laurian (Studia Universitatis Babeș-Bolyai Chemia, 2015)
The purpose of this study was to characterize the polyphenolic composition of Achillea distans and Achillea millefolium and to evaluate their antioxidant and antimicrobial activities. The total polyphenolic content was determined spectrophotometrically. The phenolic compounds were identified and quantified by HPLC-MS. The extracts were screened for antioxidant activities using two in vitro assay models: DPPH radical scavenging assay and hemoglobin ascorbate peroxidase activity inhibition (HAPX) assay. A method based on electron paramagnetic resonance (EPR) polyphenolic radicals’ detection was also described. The antimicrobial activity was determined using the disc diffusion method. For the species of Achillea, the phenolic profile showed the presence of two phenolic acid derivatives (chlorogenic and p-coumaric acids), four flavonoid glycosides (hyperoside, isoquercitrin, rutin and quercitrin) and four free flavonoids (quercetin, patuletin, luteolin and apigenin), in different concentrations. The evaluation of antioxidant activity indicated that A. millefolium extract has more antioxidant than A. distans, related with the polyphenolic total content. Both extracts showed activity against all tested bacterial species. These results suggest that the two native species of Achillea can be used as a potential source of polyphenolic compounds with bioactive properties for cosmetic and medicinal applications.